Accreditation and promotion of Spanish university lecturers: situation, trends and future prospects. - Salvador García-Ayllon Veintimilla; Antonio Tomás Espín (Universitat Politècnica de València, 2014)
The major legislative changes undertaken by the Spanish University Ordination Act in 2001 have sharply changed the guidelines of accreditation and promotion for university teachers. The period of 2001-2011 was marked by different economic and social contexts in Spanish universities, as well as by these new teacher evaluation systems coming into force. The period of economic growth until 2007 and the subsequent crisis that continues today have set boundary conditions that directly affect the structure of teaching staff in university faculties. This situation has created a problem that combines short-term phenomena such as the economic situation with long-term ones such as the teacher's accreditation process. This paper presents the evolution of teachers in Spain (associate, full professor, contracted, etc.) until 2011 and the repercussions of accreditation systems in the teaching profession. It explores the causes and consequences of different variables (such as category, dedication, or teacher's population) using the methodology of statistical analysis with the aim of determining the influence and representation that actually involves each of the existing figures in the university structure. These parameters influence teaching and it is particularly important to determine how changes in the accreditation system are actually affecting the functioning of university schools. Finally, the paper presents possible future scenarios arising in the field of university accreditation for a better fit in the international context.